Islamic history and civilization (İstanbul)
472 sayfa
Keywords: “...The first volume prepared in the context of this long-term research project with a special regional focus on South Asia, ‘Islamic History and Civilization: South Asia’, has been published. The volume is co-edited by Prof. Khurram Qadir and Prof. Faraz Anjum, both leading academic experts from the region. Prof. Khurram Qadir is the former Chair of History at Bahauddin Zakariyya University, Multan; Chairman of History at the International Islamic University, Islamabad; and the former Director of the National Institute for Historical and Cultural Research, Quaid-e Azam University. Prof. Faraz Anjum is a Senior Lecturer in History at the Punjab University, Lahore, Pakistan. The volume includes contributions by sixteen leading experts on Islamic history and civilization in the Subcontinent starting with the part on ‘Muslim Inroads in South Asia’. This part includes several articles on the early Muslim Sultanates in South Asia and detailed analyses on a variety of fields including state administration; social and economic life; science, education and culture: trade and commerce; art and architecture. The following parts of the volume highlight fragmentation of Muslim polity and focus on localized Sultanates. The Muslim polity in Baharat and Deccan regions are evaluated with reference to major states such as the Baburi/Mughal Empire; as well as the minor states that were formed after the decline of the Mughals. In this context, key historical events and development of Islamic civilization under the centralized rule of the Mughal Empire and the micro-states in frontier regions such as Balochistan, Sindh, Bhopal, Hyderabad, Awadh and Khyber are analyzed by leading experts in the field. The volume also contains general assessments concentrating on the state of South Asian Muslims during the Colonial period; Relations of the Subcontinent Muslims with the Ottoman Caliphate; and contributions of the Subcontinent to Islamic culture and civilization...“ --